The performance and QoE analysis of B2-DASH algorithm. Issue 2 (9th May 2019) - Anusas-amornkul, Tanapat; Moonsin, Surawut
Dynamic adaptive streaming over HTTP (DASH) protocol provides several video bit rates for each video segment depending on the current network conditions and it can be used for several platforms. In this paper, bandwidth and buffer-based (B 2 )-DASH algorithm is proposed to enhance DASH algorithm using both buffer and bandwidth-based approaches to provide high average video bit rate in fluctuated network conditions. B 2 -DASH is compared with FDASH algorithm, which is the best adaptive algorithm among others. This work compares the performance in low switching rate, fast switching rate, and Wi-Fi network scenarios. The performance metrics are average video bit rates, number of interruptions, and resolution changes. B 2 -DASH parameters and Quality of Experience (QoE) are analysed for the best performance for each scenario. From the analysis, B 2 -DASH outperformed FDASH in all scenarios. In Wi-Fi network scenario, the number of resolution changes was enhanced 22%, and QoE was improved 13% over FDASH.